An Analysis of Foreign Direct Investment in Indonesia from 1980 -2019 - Sawitri, Kadek Ade (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2023)
Foreign Direct Investment (FDI) has been the focus of research in the field of International Business (IB). Despite the significant development of previous studies on FDI and its role in a country, particularly in emerging economies and developing countries, this topic remains debatable. This is because pertinent FDI studies have produced inconsistent results. Another reason is that the conclusions from each analysis are distinct from one another, depending on the selection of the unit of analysis, the time frame, and the methods used to research FDI. Indonesia presents a prodigious example of how a country can transform its peak adversity to attain success. Indonesia was classified as among the poorest and most underdeveloped countries during the post-independence period. The country also experienced significant stalling in its development because of the Asian Financial Crisis (AFC) and the Global Financial Crisis (GFC). Although the country has developed and risen from its adversity, it still has the potential to grow further and compete with other emerging economies and developing countries. Therefore, conducting a comprehensive analysis of FDI in Indonesia is merited. This thesis provides insight into the progression of Indonesia's FDI relative to its economic development and the investigation of potential growth factors favouring Indonesia's sustainable economic development. The Investment Development Path (IDP) is an IB theory that can be applied to investigate the relationship between FDI and a country's economic development. By employing country-specific analysis using aggregate-level data on Indonesia, this thesis aims to investigate the role of FDI in Indonesia?s economy, the determinants of Indonesia's FDI, and the government's role in promoting FDI. This thesis comprises three studies that were synthesised to address the research aims. As one of the main theories supported in this thesis, the first study aims to review the evolution of IDP theory and the pertinent literature on IDP to investigate the potential area for further research on IDP. The second study aims to investigate the progression of Indonesia?s FDI and economic development using the IDP concept. The findings of this study are then used to derive the third study proposed in this thesis. Since Indonesia?s position on the IDP has been restricted in the second stage of the IDP due to the significant difference between Inward FDI (IFDI) and Outward FDI (OFDI), the inadequacy of domestic companies' capabilities to engage in OFDI, and no support from Indonesia's government to stimulate and boost OFDI from Indonesia. Accordingly, the third study aims to address the emerging issues regarding Indonesia?s OFDI by investigating the role of OFDI in Indonesia's economy, the determinant factors of OFDI from Indonesia, and the role of the government in promoting OFDI from Indonesia. This thesis yields support to other developing countries and emerging economies that experience a similar progression to Indonesia in investigating their FDI performance following their economic growth to promote their FDI. This thesis found that Indonesia has significant competitive advantages in attracting IFDI. Accordingly, the country has been a favourable destination for IFDI. However, the country's comparative advantages in the global market still lag behind those of other emerging economies. The government only embraces IFDI as a means of developing its economy. Nevertheless, the development of domestic companies? capabilities has not significantly upgraded with the presence of IFDI. Therefore, this thesis investigates potential areas for nurturing and promoting the development of domestic companies, thus boosting, and advancing Indonesia's comparative advantages in the global market and stimulating its sustainable economic development in the future. This thesis will benefit practices related to policymakers, researchers, and companies. The findings of this thesis can be treated as inputs for policymakers in Indonesia, other emerging economies, and developing countries in framing policies and regulations to promote their FDI, thus contributing to sustainable economic development by using the proposed frameworks for generating policies. This thesis engages in a comprehensive investigation of FDI and economic development in Indonesia, which leads to the establishment of several frameworks that can be applied to further research on emerging economies and developing countries. It also benefits companies (both MNCs and Indonesian domestic companies) that are interested in investing in Indonesia (for MNCs) or other countries (for Indonesian domestic companies), as this study can be treated as a reference for their decision-making processes. Given that this thesis pursued a macro-level analysis of FDI in Indonesia, there is a potential area for further research to investigate the micro-level analysis of FDI if domestic or international sources establish the necessary level of data, or if future research can collect primary micro-level data. This thesis also applies an underdeveloped method, such as thematic analysis for a systematic literature review, Toda-Yamamoto-Dolado-Lutkephol (TYDL) augmented Vector Autoregression (VAR) for OFDI research, and institutional analysis for IDP and OFDI research. There is a potential area for further research to apply these methods in other countries or to engage in other underdeveloped methods to conduct a similar analysis and compare the findings.
APPROVED
Keywords: Indonesia; Emerging economy; Developing country; Inward FDI; Outward FDI; Investment Development Path; Foreign Direct Investment